Evaluation of the Antibiotic Resistance in COVID 19 Infected Patients in Jeddah, Saudi Arabia-A Cross-Sectional Study - Mujamami, Ayman Hasan Ali; Raju, Akondi Butchi (Journal of Ecohumanism, 2024)
Introduction: Antimicrobial resistance (AMR) is already common in Middle Eastern countries, with limited monitoring data. The COVID-19 pandemic has worsened this issue, especially in Saudi Arabia, where overuse and misuse of antibiotics have been widely reported in hospitals and the community. This increased antibiotic use has raised concerns about accelerating AMR. This study aims to assess the prevalence, diagnosis, and treatment of antibiotic resistance in COVID-19 patients in Saudi Arabia. Methodology: This single-site, retrospective cross-sectional study analyzed medical records of 266 COVID-19 patients at King Fahad Armed Forces Hospital from March 2020 to March 2022. Descriptive statistics (SPSS v25) were used to summarize patient demographics and outcomes. Results: Most participants were male (59%) and adults (55%). Over half (52.63%) had comorbidities, mainly diabetes mellitus and hypertension. Antibiotic overuse and misuse occurred in 71.08% of patients. As a result, 18.05% developed various types of AMR. The most common multi-drug resistant bacterial co-infections were Candida species, Escherichia coli, Methicillin-resistant Staphylococcus aureus (MRSA), Klebsiella species, Pseudomonas aeruginosa, Gram-positive cocci, Enterococcus faecalis, and Streptococcus agalactiae. The highest resistance was to ceftriaxone, followed by piperacillin/tazobactam, azithromycin, oseltamivir, meropenem, and others. Conclusion: This study found a high prevalence of bacterial co-infection and AMR among hospitalized COVID-19 patients. High AMR rates threaten antibiotic effectiveness, especially in hospitals. The study recommends considering co-infections in COVID-19 management and implementing antibiotic stewardship programs, supported by standard treatment guidelines, to reduce antibiotic resistance.